Principles of Managerial Finance - Chad J. Zutter (Pearson Education Limites, 2015)
Once again, Principles of Managerial Finance brings you a user friendly text with strong pedagogical features and an easy-to-understand writing style. The new edition continues to provide a proven learning system that integrates pedagogy with concepts and practical applications, making it the perfect learning tool for today's students. The book concentrates on the concepts, techniques and practices that are needed to make key financial decisions in an increasingly competitive business environment. Not only does this text provide a strong basis for further studies of Managerial Finance, but it also incorporates a personal finance perspective. The effect is that students gain a greater understanding of finance as a whole and how it affects their day-to-day lives; it answers the question "Why does finance matter to ME?" By providing a balance of managerial and personal finance perspectives, clear exposition, comprehensive content, and a broad range of support resources, Principles of Managerial Finance will continue to be the preferred choice for many introductory finance courses."--Publisher's website